Management Information Systems in Decision Making: Narrative Review - Natalia Kristiani; Kusworo Adi; Apoina Kartini (Universitas Aisyah Pringsewu, 2021)
Management has a role in generating information, which requires the use of information systems capable of producing relevant and better data. Systematic decision-making procedures are also needed to produce more focused data. In making decisions for hospital development, hospital management considers several factors, including health programs by looking at facilities and specialist doctors who can provide excellent service, as well as efforts with good numbers and services to introduce or convince the public of our services. general, company, and insurance This research uses a narrative review approach, with many articles on the same problem. Articles are taken from a database from Scopus, Science Direct, ProQuest, SpringerLink, Google Scholar, Nature, JSTOR, and Emerald Insight with a total of 29 articles used. The purpose of this study is to determine whether management has a significant influence in decision making. decisions in hospitals with strategic support systems such as human resource development, program selection, marketing, and facility growth. Abstrak: Manajemen memiliki peranan dalam menghasilkan informasi, yang mengharuskan penggunaan sistem informasi yang mampu menghasilkan data yang relevan dan lebih baik. Prosedur pengambilan keputusan yang sistematis juga diperlukan untuk menghasilkan data yang lebih terfokus. Dalam mengambil keputusan untuk pengembangan rumah sakit, manajemen rumah sakit mempertimbangkan beberapa faktor, antara lain program kesehatan dengan melihat fasilitas dan dokter spesialis yang dapat memberikan pelayanan prima, serta usaha dengan jumlah dan pelayanan yang baik untuk memperkenalkan atau meyakinkan masyarakat akan pelayanan kami. umum, perusahaan, dan asuransi Penelitian ini menggunakan pendekatan narrative review, dengan banyak artikel tentang masalah yang sama. Artikel diambil dari data base yang berasal dari scopus, science direct, ProQuest, SpringerLink, Google Scholar, Nature, JSTOR, dan Emerald Insight dengan total artikel yang digunakan sebanyak 29. Tujuan dari penelitian ini adalah untuk mengetahui apakah manajemen memiliki pengaruh yang signifikan dalam pengambilan keputusan di rumah sakit dengan sistem pendukung strategis seperti pengembangan sumber daya manusia, pemilihan program, pemasaran, dan pertumbuhan fasilitas.